Review of Belief without Borders: Inside the Minds of the Spiritual but Not Religious - Donovan O Schaefer (Secularism and Nonreligion, 2015)
A review of Linda E. Mercadante's Belief without Borders: Inside the Minds of the Spiritual but Not Religious.